Disproportionality analysis of vibegron-associated adverse events using the FDA adverse event reporting system (FAERS): a real-world pharmacovigilance study - Bangbei Wan; Zhi Zhou; Ning Ma; Weiying Lu (European Journal of Medical Research)
Abstract Background Overactive bladder (OAB) syndrome has a significant impact on quality of life, and vibegron has emerged as a therapeutic option. This study aims to evaluate the safety profile of vibegron in a disproportionality analysis by analyzing adverse event (AE) reports from the Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods We conducted a retrospective analysis of the FAERS database from January 2021 to September 2023. After duplicate removal and thorough screening, 1137 vibegron-related AE reports were identified. We analyzed these reports for demographic and clinical characteristics, signal detection at the system organ class (SOC) level, and specific AEs. Results Females comprised a higher percentage (67.72%) of AE reports compared to males. The elderly population (age > 64 years) accounted for 15.84% of the cases. The majority (95.69%) of the reports originated from the USA. Signal detection revealed significant findings across 19 organ systems with notable SOCs, including renal and urinary disorders (ROR = 7.72, 95%CI 6.83–8.72), gastrointestinal disorders (ROR = 1.38, 95%CI 1.21–1.58), and respiratory, thoracic, and mediastinal disorders (ROR = 1.21, 95%CI 1.01–1.45). In addition, several unexpected AEs were identified, such as dry mouth, hot flush, constipation, and increased blood pressure. Conclusions This study provides comprehensive insights into vibegron's safety profile, revealing both known and unexpected AEs. The findings highlight the need for careful patient selection and monitoring, especially among females and the elderly. The results advocate for ongoing pharmacovigilance and further research to ensure vibegron's safe and effective use in OAB treatment.